Hydatid Cyst of the Uterus - A. Başgül; Z. N. Kavak; H. Gökaslan; S. Küllü (Hindawi Limited, 2001)
Background: Hydatidosis is a common zoonosis that affects a large number of humans and animals, especially in poorly developed countries. The infesting parasite has four forms named Echinococcus granulosis, E. multilocularis , E. vogeli and E. oligarthrus (very rare in humans). The most frequently involved organs are liver followed by the lung. The involvement of the genital tract is rare and the occurrence in the uterus is an extreme rarity.We report a case of hydatid cyst in the uterus.